The Impact of COVID-19 on the Clinical Experience and Training of Undergraduate Student Radiographers internationally: The Clinical Tutors' perspective. (October 2022) - Elshami, W.; Abuzaid, M.M.; McConnell, J.; Floyd, M.; Hughes, D.; Stewart, S.; McFadden, S.
Abstract: Introduction: The impact on the clinical training and education of healthcare students by COVID-19 has been documented. However, the thoughts and experiences of clinical tutors (CTs) about radiography students attending for clinical training and education during this now elongated period beyond first recognition of the virus has not been explored. This paper will discuss data collected from CTs in the UK Devolved Nations (UKDN) and the United Arab Emirates (UAE) who were compared because of their similarities in delivery based on individual 'rules of engagement' devised by their various health departments. Aim: The purpose of this study was to examine the clinical tutors' thoughts and experiences of supervising radiography students attending clinical placement during the COVID-19 pandemic. Methods: The UK Devolved Nations (UKDN) and the United Arab Emirates (UAE) were selected for comparison on an international level as they are geographically distinct with a comparable population and education accredited/acknowledged by the Society and College of Radiographers (SCoR). Data was collected data from CTs across the UKDN and the UAE. The study used an online questionnaire (Google Forms) with closed questions in four themes including: students' experiences, impact on students' clinical placement, attitude of the clinical staff and the potential effects of COVID-19 on future graduates' skills and competencies. Further data was gathered on the experience of CTs mentoring students during the COVID-19 pandemic. Results: Data were collected from 59 CTs (81%, n = 48) from UKDN and (19%, n = 11) UAE. Twenty-seven (46%) respondents reported that COVID-19 had a negative impact on clinical practical experience. However, 32 (54%) identified that COVID-19 had no impact on student supervision/feedback or on clinical achievements. Eleven (19%) respondents thought that students should not have been on clinical placement during the pandemic but a further 51% (n = 30) were happy with the students on placement and expressed willingness to delegate work to students. Interestingly, 58% (n = 34) of CTs suggested that future graduates may need a longer preceptorship after they graduate due to receiving decreased clinical experience during the pandemic. Overall, 78% (n = 46) of respondents thought that students improved their clinical confidence by working directly with COVID-19 positive patients. Conclusion: The current study has identified conflicting opinions across CTs in different clinical departments. Whilst some felt that students should not be in the hospital during the pandemic, others reported that working directly with COVID-19 patients had a positive impact on students as it improved their clinical confidence. Despite the challenges presented by COVID-19, CTs were able to provide direct clinical supervision and feedback to students on clinical placement throughout the pandemic. Nevertheless, future graduates may need a longer preceptorship period due to decreased clinical experience during the pandemic. Implications for practice: Clinical placements should continue during subsequent COVID-19 waves of infection or future pandemics to ensure development of skills in resilience and adaptability. Underdeveloped skills due to a decreased range of examinations can be rectified when any wave of the infection subsides by providing tailored training based on individual student's needs.